Pengaruh Keragaman Produk Dan Harga Terhadap Keputusan Pembelian Kain Batik Papua (Studi Kasus: Toko Batik Papua Kota Sorong) - Welly Salomi Yable; Susana Magdalena Welly Muskita (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
Batik is the work of the Indonesian people which is a combination of art and technology by the ancestors of the Indonesian nation. Indonesian batik can develop to an unparalleled level both in design/motif and process. A variety of batik patterns that contain full meaning and philosophy. This research aims to find out how the diversity of products. This sampling method ensures that the sample is representative of the target population and can be used to make conclusions that can be applied to the entire population. The data analysis method used in this study is the regression analysis method. This regression analysis method involves using statistical models to evaluate the relationship between independent variables (product diversity) and dependent variables (buyer consumer satisfaction). Based on the gender respondent table above, 80 respondents who were the subjects of this study were about 60 (25.00%) men and about (20 75.00%) respondents from the age of 18 respondents, and about 20 (20.25%) of respondents' data based on age, there were 80 respondents who were sampled in this study, respondents aged 18 about 25 or (31.25%) and From the data above, there is also an age of 1924 years around 32 respondents or (40.00%) and for that 25-year-old respondents Diversity affects consumer satisfaction, which means that the more consumers are interested in the diversity of products sold, the higher, in the decision to buy Papuan batik cloth is good. In the purchase decision variable in general, it is at a good interpretation value Then Papuan batik fabric must offer a price that is in accordance with consumer power, because that way it can attract buyers' interest so that consumers do not switch to competitors who have a fairly cheaper price.